Italian's scandalous marriage plan - Fuller, Louise (Romance author) (Harlequin presents, 2021)
"In mere months, Juliet Castellucci has gone from fairy-tale Verona wedding to a union in tatters. Convinced her husband, Ralph, has betrayed her, she demands a divorce...which means denying her still-sizzling attraction to him! Ralph can't prove his innocence if Juliet won't talk to him--so he whisks her away without warning for a night of reconciliation aboard his yacht. Sparks fly as the star-crossed pair give in to passion--a tempting reminder of the heat that will make or break their marriage!" -- Page [4] cover.